Location optimization of dairy processing - Reecy, Michael (Kansas State University, 2018)
Location optimization of a new dairy processing plant is crucial given the significant capital investment of $350 million required to build the plant. Couple this with notable differences in milk and transportation costs due to location, an examination of historical Net Present Value (NPV) of Earnings Before Interest, Taxes, Depreciation and Amortization (EBITDA) adjusted by a discount rate of 3% is warranted to help determine the most optimal location for a new dairy processing plant investment. This thesis is an examination of historical EBITDA NPV for three locations: Dumas, TX, Sioux Falls, SD, and Lansing, MI in an effort to predict the optimal location of a future dairy processing plant. These locations were chosen due to each having the necessary milk supply that would both encourage milk production and support increases in dairy processing. Prices dairy processors receive for cheese can fluctuate but are not tied to the location in which the cheese is produced. Transportation costs of the cheese are determined by the distance to the processing plant from Plymouth, WI, which is where most further cheese processing takes place. Therefore, this thesis includes a sensitivity analysis for the Lansing, MI location to determine a breakeven milk cost and cheddar cheese price. The NPV was positive for the Dumas, TX location at $100 million as compared to (-$820) million and (-$247) million at the Sioux Falls, SD and Lansing, MI locations, respectively. The results indicate an emerging EBITDA NPV trend favoring the Lansing, MI location as indicated by this location having the best performance in the last two years (2016-2017) of $104 million compared to a negative performance at both of the other locations. The previous 8 years performance would favor the Dumas, TX location, however more weight was given to the past 2 years performance as an indicator for future economic returns. As a result, this thesis concludes the Lansing, MI location as the most favorable location for a new dairy processing investment.
Keywords: Dairy; Location problem; Logistics; Net present value; Supply chain management